Determination of the ligand pharmacophore required for secondary conformation activation of the human β1-adrenoceptor - Pinto de Sousa, Emanuel (2020)
The β1-adrenergic receptor exists in at least two different agonist conformations: a primary conformation where endogenous catecholamines and β-blockers bind, and where agonist responses are blocked by low concentrations of antagonists and a secondary conformation, for which the precise nature is unknown, through which responses are more resistant to blockade by conventional primary conformation antagonists. Conventional agonists such as isoprenaline and cimaterol stimulate a response mainly through the primary conformation, while others such as alprenolol and oxprenolol can mediate a response through both conformations of the β1-AR, though the response mediated through the secondary conformation requires a higher concentration of ligand. Other ligands, such as CGP12177, behave as non-conventional agonist and bind with high affinity to the primary conformation (blocking the response of conventional agonist) but then, at much higher concentrations, stimulate a response through the secondary conformation. Only ligands with higher affinity for the primary conformation than for the secondary have been identified so far.